2011
DOI: 10.1093/jac/dkr403
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of tedizolid (TR-700) against linezolid-resistant staphylococci

Abstract: The results of this study confirm the activity of tedizolid against linezolid-resistant staphylococci. This new oxazolidinone could have an important role as a potential therapeutic agent against multidrug-resistant staphylococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 9 publications
2
45
0
2
Order By: Relevance
“…The results suggest that TR-701 would exhibit an efficacy similar to the efficacy of lin- ezolid for S. aureus pneumonia. An unanswered question in the current study is whether TR-701 would be expected to have the same efficacy for a linezolid-resistant isolate, as has been suggested by in vitro results (32,33,46,49). The results suggest further study of TR-701 in clinical trials of pneumonia due to S. aureus is warranted and may be especially useful given the increased burden of MSSA and MRSA pneumonia in the health care setting.…”
Section: Discussionmentioning
confidence: 73%
“…The results suggest that TR-701 would exhibit an efficacy similar to the efficacy of lin- ezolid for S. aureus pneumonia. An unanswered question in the current study is whether TR-701 would be expected to have the same efficacy for a linezolid-resistant isolate, as has been suggested by in vitro results (32,33,46,49). The results suggest further study of TR-701 in clinical trials of pneumonia due to S. aureus is warranted and may be especially useful given the increased burden of MSSA and MRSA pneumonia in the health care setting.…”
Section: Discussionmentioning
confidence: 73%
“…The introduction of TZD provides another potential antimicrobial with an efficacy against these organisms, and early MIC studies performed with bacterial species show that TZD has a 4-to 16-fold greater potency than LZD against some bacteria, including LZD-resistant organisms (2,15,16 50 and an MIC 90 of 64 g/ml for LZD, and isolates were not differentiated into subspecies (current subspecies designations were unknown at the time) as they were in this study of 81 isolates of M. abscessus subsp. abscessus (MIC 50 , 4 g/ml and MIC 90 , 8 g/ml for TZD; MIC 50 , 16 g/ml and MIC 90 , 32 g/ml for LZD).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have also reported that TZD has enhanced in vitro activity against bacterial strains, including linezolid (LZD)-resistant strains of Streptococcus pneumoniae and methicillin-susceptible and -resistant coagulase-negative and -positive Staphylococcus, Streptococcus pyogenes, and Streptococcus agalactiae (2,3,8). With this superior activity in mind, we undertook a large study to evaluate the in vitro MICs of TZD compared with the MICs of LZD and other comparator antimicrobials against isolates of NTM.…”
mentioning
confidence: 99%
“…In a study of its activity against linezolid‐resistant staphylococci, tedizolid showed a more than 16‐fold improvement compared to linezolid 39. It also maintained activity against most of the tested isolates, including multidrug‐resistant ones, thus clearly demonstrating the benefit of the structure‐based approach.…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 92%